Analysis of the judgment of the Case of The Last Temptation of Christ (Olmedo Bustos et al.) vs. Chile of the Inter-American Human Rights Court - Fernández Torres, Elena (2019)
The Inter-American Court of Human Rights analyzes about the possible infringement of the freedoms of thought and expression in contrast with freedoms of conscience and religious, against the judicial censure enforcement for the communication and outreach of “The Last Temptation of Christ”. In addition, it analyzed the obligation of respect from the Chilean Estate, in order to enforce the rights and duties from The American Convention on Human Rights, about those rights and the state responsibility. According to this, we are interested in deepen from the Critical Theory into the tension between Formal Law -as a power manifestationand Art, from the political and axiological Law dimension. Finally, this text thinks over the effectiveness of the judgment.